2019
DOI: 10.1051/0004-6361/201834376
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the k2 Love number of WASP-18Ab from its radial velocity measurements

Abstract: Context. Increasing our knowledge of the interior structure, composition and density distribution of exoplanets is crucial to make progress in the understanding of exoplanetary formation, migration and habitability. However, the directly measurable mass and radius values offer little constraint on interior structure, because the inverse problem is highly degenerate. Therefore there is a clear need for a third observable of exoplanet interiors. This third observable can be the k 2 fluid Love number which measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…While spectroscopically detected apsidal motions were previously reported for other close binaries (see e. g Ferrero et al 2013). and even for an exoplanet(Csizmadia et al 2019), too, we are not aware of any other systems where such a significant fraction of a complete apsidal revolution period was covered with RV data so densely as in the present case. 11 Note, that the combination of the dynamical and geometrical effects on the light-and ETV curves break the degeneracy between prograde and retrograde solutions, therefore an almost coplanar, but retrograde solution can be ruled out with high confidence.MNRAS 000, 1-19(2019)…”
mentioning
confidence: 60%
“…While spectroscopically detected apsidal motions were previously reported for other close binaries (see e. g Ferrero et al 2013). and even for an exoplanet(Csizmadia et al 2019), too, we are not aware of any other systems where such a significant fraction of a complete apsidal revolution period was covered with RV data so densely as in the present case. 11 Note, that the combination of the dynamical and geometrical effects on the light-and ETV curves break the degeneracy between prograde and retrograde solutions, therefore an almost coplanar, but retrograde solution can be ruled out with high confidence.MNRAS 000, 1-19(2019)…”
mentioning
confidence: 60%
“…Based on this equation, along with the precession period from the best-fitting apsidal precession model, we found that the maximum deviation between the RV signal of a precessing orbit with parameters in Table 6 and a circular model would be ∼ 6 m s −1 over a decade. We note that Csizmadia et al (2019) claimed that apsidal precession would result in residuals on the order of K orb ; however that only holds if the anomalistic period could be determined independently. In reality, the anomalistic period would need to be determined using the same data, and the residuals would be on the order of eK orb .…”
Section: Joint Rv-timing Fitmentioning
confidence: 81%
“…As for apsidal precession, Csizmadia et al (2019) presented a formula for the associated RV signal: RV = K [e cos ω(t) + cos (ν + ω(t)) +ω n 1 − e 2 3/2 cos (ν + ω(t)) 1 + e cos ν…”
Section: Joint Rv-timing Fitmentioning
confidence: 99%
“…periastron precession (cf. Csizmadia, Hellard & Smith 2019), gravitational interaction by a third body (moon, planet(s), brown dwarf, or other star in the system (e.g. Borkovits et al 2011)), magnetic interaction between the star and the planet, mass-loss from the system via stellar wind or by the evaporation of the planet, etc.).…”
Section: Introductionmentioning
confidence: 99%